Concentrations, Spatial Distributions, and Sources of Heavy Metals in Surface Soils of the Coal Mining City Wuhai, China. (22nd July 2020) - Bu, Qingwei; Li, Qingshan; Zhang, Handan; Cao, Hongmei; Gong, Wenwen; Zhang, Xin; Ling, Ke; Cao, Yibo
Abstract : Various studies have shown that soils surrounding mining areas are seriously polluted by heavy metals. In this study, 58 topsoil samples were systematically collected throughout the coal mining city Wuhai, located within the Inner Mongolia Autonomous Region of China. The concentrations of As, Hg, Cr, Ni, Cu, Zn, Cd, and Pb in these samples were measured and statistically analyzed. The mean concentrations of all heavy metals were lower than their Grade I values defined by the Chinese Soil Quality Standard. However, the mean concentrations of individual heavy metals in many samples exceeded their background values. The spatial distribution of heavy metals was analyzed by the ordinary kriging interpolation method. The positive matrix factorization model was used to ascertain contamination sources of the eight heavy metals and to apportion the contribution of each source. The most severely polluted area was the Wuhushan mine site in the Wuda district of Wuhai. Our results showed that coal mining strongly affected heavy metal contamination of the local soils. Results of source apportionment indicated that contributions from industrial activities, atmospheric deposition, agricultural activities, and natural sources were 31.3%, 26.3%, 21.9%, and 20.5%, respectively. This clearly demonstrates that anthropogenic activities have markedly higher contribution rates than natural sources to heavy metal pollution in soils in this area.